Coating Effect on the 1H—NMR Relaxation Properties of Iron Oxide Magnetic Nanoparticles - Francesca Brero; Martina Basini; Matteo Avolio; Francesco Orsini; Paolo Arosio; Claudio Sangregorio; Claudia Innocenti; Andrea Guerrini; Joanna Boucard; Eléna Ishow; Marc Lecouvey; Jérome Fresnais; et al. (Nanomaterials, 2020)
We present a 1H Nuclear Magnetic Resonance (NMR) relaxometry experimental investigation of two series of magnetic nanoparticles, constituted of a maghemite core with a mean diameter dTEM = 17 ± 2.5 nm and 8 ± 0.4 nm, respectively, and coated with four different negative polyelectrolytes. A full structural, morpho-dimensional and magnetic characterization was performed by means of Transmission Electron Microscopy, Atomic Force Microscopy and DC magnetometry. The magnetization curves showed that the investigated nanoparticles displayed a different approach to the saturation depending on the coatings, the less steep ones being those of the two samples coated with P(MAA-stat-MAPEG), suggesting the possibility of slightly different local magnetic disorders induced by the presence of the various polyelectrolytes on the particles’ surface. For each series, 1H NMR relaxivities were found to depend very slightly on the surface coating. We observed a higher transverse nuclear relaxivity, r2, at all investigated frequencies (10 kHz ≤ νL ≤ 60 MHz) for the larger diameter series, and a very different frequency behavior for the longitudinal nuclear relaxivity, r1, between the two series. In particular, the first one (dTEM = 17 nm) displayed an anomalous increase of r1 toward the lowest frequencies, possibly due to high magnetic anisotropy together with spin disorder effects. The other series (dTEM = 8 nm) displayed a r1 vs. νL behavior that can be described by the Roch’s heuristic model. The fitting procedure provided the distance of the minimum approach and the value of the Néel reversal time (τ ≈ 3.5 ÷ 3.9·10−9 s) at room temperature, confirming the superparamagnetic nature of these compounds.